KOMUNIKASI EMPATI PENGASUH DALAM POLA PENGASUHAN ANAK TERLANTAR DI PANTI SOSIAL PENGASUH ANAK (PSPA) KOTA PEKANBARU - Nova Yohana; Rum yeni; Zalaila Sudarningsih; Salsa bila (Jurnal Ranah Komunikasi, 2021)
The orphanage is a place where neglected children receive their physical needs, such as a place to live, as well as their spiritual needs, which are met by foster parents or caregivers. Caregivers can act as parents by providing neglected children with attention, affection, and a sense of security at the Pekanbaru City Social Care Center (PSPA), which is fully supervised by the Riau Province Social Service. Parenting neglected children is based on empathic communication. The purpose of this research is to determine the affective and cognitive aspects of empathic communication that occurs between caregivers and neglected children in the formation of an attitude of independence at the UPT Panti Social Caregivers (PSPA) Pekanbaru City. This is a qualitative research method with a humanistic perspective. Data for this study were gathered through observation, interviews, and documentation. Data reduction, data presentation, and conclusions were used in technical data analysis. Participation extension and triangulation are used in the data validity technique. The finding showed that the affective aspect of empathic communication used by caregivers to foster the independence attititude of abandoned children was founded on deep feelings, sympathy and empathy, and a sense of care. Cognitive aspects of empathic communication between caregivers and abandoned children are formed through good relationships and the nature of similarity. Caregivers have a big responsibility in protecting abandoned children in social institutions so that they can be independent.